INTERMEDIATION OF ISLAMIC COMMERCIAL BANKS IN REAL TIME GROSS SETTLEMENT TRANSACTIONS OF ISLAMIC BANKING IN INDONESIA - Muhamad Halik; Akhmad Nur Zaroni; Dedy Mainata (Journal of Management and Islamic Finance, 2022)
BI-RTGS is transferring funds with an essential function in the payment system and third-party funds as a factor to meet the current account balance which is a condition for BI-RTGS transactions. Bank financing is considered to be able to affect the number of BI-RTGS transactions. This research used 14 Islamic commercial banks registered as BI-RTGS participants. The results show that Islamic Commercial Bank Third Party Funds have a partial effect on the nominal amount of BI-RTGS transactions. Islamic Commercial Bank Financing has a partial effect on the nominal amount of BI-RTGS transactions. Third Party Funds and Islamic Commercial Bank Financing simultaneously affect the nominal amount of BI-RTGS transactions. In the determination coefficient test, the R Square value of third-party funds is 11.3% and financing is 4.1%. This means that the influence of third party funds is greater than the amount of the influence of financing on the nominal amount of BI-RTGS transactions in Islamic Banking in Indonesia.